2018
DOI: 10.1016/j.nwh.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of Cervical Cancer Screening in Transgender Men

Abstract: Most female-to-male (FTM) transgender men retain their cervixes and need comprehensive sexual health care, including cervical cancer screening. According to the literature, FTM individuals obtain cervical cancer screening less frequently and are less likely to be up to date on their Pap tests compared with cisgender women. Misinformation related to human papillomavirus and cervical cancer risk was noted for health care providers and FTM individuals. Absence of transgender-specific guidelines or trained health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 28 publications
2
57
0
Order By: Relevance
“…Although further study of the cervical cancer screening needs and practices of transgender, gender non‐binary, and intersex populations is needed, this is beyond the scope of this review . Two recent reviews summarize the experiences of transgender men seeking cervical cancer screening and the disparities faced by this population …”
Section: Methodsmentioning
confidence: 99%
“…Although further study of the cervical cancer screening needs and practices of transgender, gender non‐binary, and intersex populations is needed, this is beyond the scope of this review . Two recent reviews summarize the experiences of transgender men seeking cervical cancer screening and the disparities faced by this population …”
Section: Methodsmentioning
confidence: 99%
“…5 A literature review of cervical cancer screening among people who are FTM transgender also reported that they were less likely to be up to date on Pap test screening; among those who did receive screening, they were more likely to have abnormal or inadequate results compared with women who were cisgender. 8 There are many factors that may precipitate this disparity. Patients who are FTM transgender and health care providers may misperceive sexual history risk.…”
Section: Cervical Cancer Screeningmentioning
confidence: 99%
“…10 This disparity is likely further exacerbated by the fact that patients who are transgender regularly experience stigmatization and discrimination in the health care setting. 5,8 Primary care providers should consider how to improve the experience of and access to screening for malignant disease in patients who are transgender. To this effect, a recent publication reporting on best practices based on qualitative interviews with patients who are transgender and clinicians experienced in caring for this patient population is an excellent resource for health care providers.…”
Section: Cervical Cancer Screeningmentioning
confidence: 99%
“…4 3 Transgender men with a cervix are less likely than cisgender women to have up-to-date Papanicolaou screening In a literature review, transgender men with a cervix were 8.3 times more likely to have an inadequate Pap test, related to testosterone-induced physical changes and examination discomfort for provider and patient, and less likely to be screened appropriately (64.3% v. 73.5%) than cisgender women. 5 Individuals should be kept on the recall list for regular cervical screening. Providers should be trained on transgender-inclusive Pap testing, which can include a baseline Pap test before starting testosterone; short-term topical estrogen before the test; topical lidocaine to the vaginal introitus; use of a pediatric or long, narrow speculum; informing individuals that test results may be inadequate; and communication that prioritizes dignity and autonomy.…”
Section: Medical Guidelines On Providing Care For Transgender Individmentioning
confidence: 99%